Adult hippocampal ganglioneuroblastoma: Case report and literature review. Issue 51 (December 2017) - Yao, Pei-Sen; Chen, Guo-Rong; Shang-Guan, Huang-Cheng; Lin, Qing-Song; Wang, Xing-Fu; Zheng, Shu-Fa; Kang, De-Zhi
Abstract: Rationale: Intracranial ganglioneuroblastoma represents a rare subtype of primitive neuroectodermal tumor. Here, we report a hippocampal ganglioneuroblastoma and a literature review of cerebral anglioneuroblastoma is carried out. Patient concerns: We report a 16-year-old male patient presenting with absence seizure and high-infiltration hippocampal ganglioneuroblastoma. Interventions: Magnetic resonance imaging (MRI) indicates a space-occupying lesion with a well-defined margin in the right temporal lobe and hippocampus. However, hyper-signal on flair and diffusion-weighted imaging (DWI) with a low apparent diffusion coefficient (ADC) value is detected, which prompts high tumoral invasiveness. Interventions: A total resection of tumor and subsequent chemotherapy combing with radiotherapy is performed. Outcomes: For a follow-up period of 60 months, no evidence of recurrence and further seizures are detected. Lessons: High-infiltration hippocampal ganglioneuroblastoma is a rare event. MRI examination often showed features of low-grade gliomas, while hyper-signal lesion on DWI with a low ADC value can be detected. Complete resection combined with fractionated radiotherapy and chemotherapy was the optimal treatment for cerebral ganglioneuroblastoma.